The cardio-oncologic burden of breast cancer: molecular mechanisms and importance of preclinical models - Brauer, Jannek; Tumani, Mikail K.; Frey, Norbert; Lehmann, Lorenz (Basic research in cardiology, 2025)
Breast cancer, the most prevalent cancer affecting women worldwide, poses a significant cardio-oncological burden. Despite advancements in novel therapeutic strategies, anthracyclines, HER2 antagonists, and radiation remain the cornerstones of oncological treatment. However, each carries a risk of cardiotoxicity, though the molecular mechanisms underlying these adverse effects differ. Common mechanisms include DNA damage response, increased reactive oxygen species, and mitochondrial dysfunction, which are key areas of ongoing research for potential cardioprotective strategies. Since these mechanisms are also essential for effective tumor cytotoxicity, we explore tumor-specific effects, particularly in hereditary breast cancer linked to BRCA1 and BRCA2 mutations. These genetic variants impair DNA repair mechanisms, increase the risk of tumorigenesis and possibly for cardiotoxicity from treatments such as anthracyclines and HER2 antagonists. Novel therapies, including immune checkpoint inhibitors, are used in the clinic for triple-negative breast cancer and improve the oncological outcomes of breast cancer patients. This review discusses the molecular mechanisms underlying BRCA dysfunction and the associated pathological pathways. It gives an overview of preclinical models of breast cancer, such as genetically engineered mouse models, syngeneic murine models, humanized mouse models, and various in vitro and ex vivo systems and models to study cardiovascular side effects of breast cancer therapies. Understanding the underlying mechanism of cardiotoxicity and developing cardioprotective strategies in preclinical models are essential for improving treatment outcomes and reducing long-term cardiovascular risks in breast cancer patients.